2019
DOI: 10.3390/molecules24244442
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Guided Isolation of Prospective Bioactive Constituents from Roots of Clausena indica (Dalzell) Oliv

Abstract: Clausena indica fruits are routinely used for the culinary purpose as natural spices, whereas leaves and roots are folk medicine with various health benefits in southern China, South and Southeast Asia. In this study, the bioassay-guided fractionation by column chromatography yielded three pure compounds including dentatin, nordentatin, and clausine K and five active fractions (Re1-5) from C. indica roots. These known anticancer compounds were confirmed by X-ray diffraction, 1H-, 13C-nuclear magnetic resonance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 47 publications
(81 reference statements)
0
13
0
Order By: Relevance
“…After that, the enzymatic reaction was inaugurated by supplying 50 µL of L-tyrosine solution. After 10 min of incubation at the same condition, the final solution’s absorbance was recorded at 470 nm [ 72 ]. DMSO and kojic acid were used as negative control and standard inhibitor, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…After that, the enzymatic reaction was inaugurated by supplying 50 µL of L-tyrosine solution. After 10 min of incubation at the same condition, the final solution’s absorbance was recorded at 470 nm [ 72 ]. DMSO and kojic acid were used as negative control and standard inhibitor, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…This anticancer substance can be found in a wide range of Clausena species [19,[28][29][30]. On the other hand, dentatin was isolated and purified from C. indica roots in our previous study, in which, the compound was found to possess a negligible effect on antioxidants and no activity on anti-α-amylase [7]. Therefore, dentatin is not a major substance responsible for the potent biological activities of T4 but might have a role as a co-factor.…”
Section: Discussionmentioning
confidence: 95%
“…A wide range of phytochemical components can be isolated from the Clausena genus, of which coumarins, carbazole alkaloid, and sesquiterpenes are the most abundant compounds, which might have potential for anticancer activity [3][4][5][6]. In the previous study of Quan et al [7], C. indica roots were announced to have multiple biological activities comprising of antioxidant, anti-α-amylase and anti-tyrosinase. In addition, three pure anti-carcinogenic compounds including dentatin, nordentatin, and clausine K were isolated and purified from C. indica roots [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the development of antidiabetic agents from C. indica roots has been investigated by bioguided isolation of the ethyl acetate extract. The isolates, dentatin, clausine K, and nordentatin, demonstrate anti- α -amylase activity suggesting the hypoglycemic activity of C. indica roots [ 52 ]. A recent study with ethyl acetate and hexane extracts of C. indica fruit identified coumarins as major compounds demonstrating anti- α -amylase activity [ 53 ].…”
Section: Beneficial Pharmacological Activities Of M Koenigii M Minutum and C Indica mentioning
confidence: 99%